Comparative Evaluation of Students’ Performance in Campus Recruitment of a Technical Institution through Fuzzy-Multi Criteria Decision Making Techniques - Mondal, Sukarna Dey; Ghosh, Dipendra Nath (International Journal of Computer Sciences and Engineering, 2025)
In today’s world Campus placements at any Technical college in India and in the life of any student/graduate are very defining moments that students look up to and prepare themselves thoroughly to score high and well but as well as to impress their potential future employers. It is the one time that students get a precise chance to make that practical application of their technical and employable soundness to the representatives of the corporate management of the particular industry they opted for or chose in the first place. Campus Placement is a process of performance evaluation of each selected candidates with respect to some pre-assigned specific criteria by the experts. For these, an attempt has been made here to assessment of some criteria by (TOPSIS) ―Technique for Order Preference by Similarity to Ideal Solution‖ and (AHP) ―Analytical Hierarchy Process‖ under Interval Type-1 fuzzy environment (IT1F) and Interval Type-2 fuzzy environment (IT2F). These factors for Placement system are identified through the different company’s placement procedure. Here several experts gave their opinion on the basis of students’ performance. The result showed that the proposed model yields more realistic way to evaluate the performance for each student according to pre assigned criteria